EXPERIENCE ON TRANSPERITONEAL LAPAROSCOPIC DIVERTICULECTOMY IN UROLOGY DEPARTMENT HASAN SADIKIN HOSPITAL BANDUNG - Ferdian, Vicky; Pramod, Sawkar Vijay (Indonesian Urological Association, 2015)
Objective: To described our experiences in treating large bladder diverticulum using transperitoneal laparoscopic techniques in Urology Department Hasan Sadikin Hospital, Bandung. Material & method: There were 3 patients with bladder diverticulum due to bladder outlet obstruction. There are 2 males and 1 female patients. The bladder outlet obstruction was caused by BPH in both male patients and urethral stenosis in female patient. The bladder diverticles were located in left lateral bladder wall in 2 patients and right lateral bladder wall in 1 patient. All the patients underwent two stages procedure. Initially, we perform correction of the obstruction. Next stages were transperitoneal laparoscopic diverticulectomy. Result: The operating time was improving in each procedure, with average time was 180 minutes. Drain was removed in 3 days in one patient and 2 days in 2 patients. Cystostomy was removed in POD 14 in all patients. One month post operatively, we performed cystography and all of the patients had a normal result without any extravasation. The patients was discharge on day 7 in one patient and day 4 in 2 patients post operatively, with minimal pain. Until now, patient was still under follow up and no major complication was found. Conclusion: Transperitoneal laparoscopic diverticulectomy is a save alternative for the management of bladder diverticulum with minimal post-operative pain and length of stay.